Carboxymethyl Cellulose (CMC) as a Template for Laccase-Assisted Oxidation of Aniline - Shim, Euijin; Noro, Jennifer; Cavaco-Paulo, Artur; Kim, Hye Rim; Silva, Carla (Frontiers in Bioengineering and Biotechnology, 2020)
Polyaniline (PANi) is a conducting polymer which has been subject of intensive research on the exploitation for new products and applications. In this work we study the role of carboxymethyl cellulose (CMC) as a template for the in situ polymerization of aniline. Bacterial cellulose (BC) was used as the supporting material for the entrapment of CMC and for the in situ oxidation reactions. The amount of CMC entrapped onto BC was optimized as well as the conditions for laccase-assisted oxidation of aniline. The new oligomers and/or polymers were evaluated by spectrometric techniques, namely 1H NMR and MALDI-TOF, and the functionalized BC surfaces were analyzed by TGA, FTIR, XRD, SEM and reflectance spectrophotometry. The conductivity of the developed materials was evaluated using the four-probe methodology. The polymers obtained after reaction in the presence of CMC as template display a similar structure as when the reaction is conducted only in BC. Though, after oxidation in the presence of the template, the amount of oligomers/polymers entrapped onto BC is considerably higher conferring to the substrates greater electrical conductivity and coloration. The use of CMC as a template for aniline oxidation on BC seems to be a promising and cheap strategy to improve the yield of functionalization and increment the properties of the materials, namely electrical conductivity and coloration.